Exchange of Notes to amend the Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Russian Federation on Science and Technology Cooperation, Done at Moscow on 28 May 1996 as amended by the Exchange of Notes done at London on 21 April 2006 and 28 May 2006. Moscow, 12 May 2016 and 8 August 2016. ([2016-12-08]) - Unknown
No abstract available